Usability of violin and viola shoulder rest (Per Musi, 2015)
The attributes required for product development can be assessed and verified by usability. For musicians of violin and viola, accessories as shoulder rest are needed to improve the position, to minimize muscle tension in the neck and release the left hand for typing the notes. Even so problems such as musculoskeletal complaints are reported in the literature. Therefore, this study evaluated the shoulder rest used by 10 musicians from an orchestra using the principles of usability, and investigates the musicians perception related to satisfaction, effectiveness and efficiency of them, using questionnaires with open questions. The problems are related to usability being the shoulder rests considered effective to instrumental practice and they need to be more efficient, making the correct posture maintained and minor musculoskeletal events are generated due to the inadequate settings of accessories.